Pengaruh Massage Lumbal terhadap Penurunan Intensitas Nyeri pada Ibu Bersalin Kala 1 Fase Aktif - Vitri Verin; Laily Prima Monica (Journal of Ners and Midwifery, 2015)
The lumbar massage can decrease pain intensity in the childbirth, because it can helping medical patient feel fresh, relax and comfortable. Method: This research used pre experimental design with â€ one group pratest- post test design. The population of the research was the medical patient at the first period phase active in the region of Puskesmas Slumbung Kec.Gandusari Kab.Blitar. This statistical test using wilcoxon and SPSS for windows. Result: The result of the experiment showed there was an effect of the lumbar massage to the decrease of the pain intensity of medical patient at the first period phase. Based on the table of 4.6 showed that there was reduction percentage intensity pain childbirth before an after give lumbar massase, it was serious pain from 87,5% to be 25%. There was a reduction in pain intensity in childbirth to be medium intensity pain 75%. It showed the reduction from high to low. Based on statistical test Wlicoxon Signed Rank Test was obtained p value = 0.008, so the p value = 0,008 <ï¡ = 0.05, indicated an effect of lumbar massage to the decrease of maternal pain intensity in the first stage of the active phase. Result: With the lumbar massage expected to be an alternative to reduce pain during childbirth.